Placental Protein 13 (PP13) – A Placental Immunoregulatory Galectin Protecting Pregnancy - Than, Nándor Gábor; Balogh, Andrea; Romero, Roberto; Kárpáti, Éva; Erez, Offer; Szilágyi, András; Kovalszky, Ilona; Sammar, Marei; Gizurarson, Sveinbjorn; Matkó, János; Závodszky, Péter; Papp, Zoltán; et al. (Frontiers in Immunology, 2014)
Galectins are glycan-binding proteins that regulate innate and adaptive immune responses, and some confer maternal-fetal immune tolerance in eutherian mammals. A chromosome 19 cluster of galectins has emerged in anthropoid primates, species with deep placentation and long gestation. Three of the five human cluster galectins are solely expressed in the placenta, where they may confer additional immunoregulatory functions to enable deep placentation. One of these is galectin-13, also known as Placental Protein 13 (PP13). It has a “jelly-roll” fold, carbohydrate-recognition domain and sugar-binding preference resembling to other mammalian galectins. PP13 is predominantly expressed by the syncytiotrophoblast and released from the placenta into the maternal circulation. Its ability to induce apoptosis of activated T cells in vitro, and to divert and kill T cells as well as macrophages in the maternal decidua in situ suggests important immune functions. Indeed, mutations in the promoter and an exon of LGALS13 presumably leading to altered or non-functional protein expression are associated with a higher frequency of preeclampsia and other obstetrical syndromes, which involve immune dysregulation. Moreover, decreased placental expression of PP13 and its low first trimester maternal serum concentrations are associated with elevated risk of preeclampsia. Indeed, PP13 turned to be a good early biomarker to assess maternal risk for the subsequent development of pregnancy complications caused by impaired placentation. Due to the ischemic placental stress in preterm preeclampsia, there is an increased trophoblastic shedding of PP13 immunopositive microvesicles starting in the second trimester, which leads to high maternal blood PP13 concentrations. Our meta-analysis suggests that this phenomenon may enable the potential use of PP13 in directing patient management near to or at the time of delivery. Recent findings on the beneficial effects of PP13 on decreasing blood pressure du